Public markets in the City of Belém, Pará State, Brazil: inventory of commercialized fish and hygienic-sanitary conditions (Research, Society and Development, 2020)
The objective of the present work was to carry out an inventory of the fish commercialized in the public markets of the city of Belém, Pará, as well as to register the hygienic-sanitary conditions inside the establishments. This research is of a qualitative and quantitative nature, exploratory of field, transversal, carried through in six public markets of the city of Belém, observing mainly the use of Personal Protective Equipment of the manipulators, the materials used in the benches and cutting boards, the use of ice during the fish exhibition, the type of scale used, in addition to the fish species sold. The fish species most found in the markets were Dourada, Pescada Gó and Pescada Amarela. What was most observed was the exposure of the fish for sale directly on the surface of the bench, without the presence of ice. The material most commonly used in the workbenches was stainless steel which is in compliance with current legislation and the most used material in cutting boards was polyethylene, which is in compliance with the standards. It was observed the more frequent use of mechanical scales in comparison to digital scales and, in relation to the manipulators, the use of white clothes was frequent. The public markets in Belém have a wide variety of fish, with hygienic-sanitary problems that compromise the quality of products and, consequently, public health. Understanding the main obstacles and bottlenecks that prevent adjustments to the legislation, listening to the main questions of the manipulators, regarding working conditions, technical knowledge and personal hygiene, would be important to understand the current problems.